Evaluasi Stabilisator Agar-Agar dan CMC Sediaan Sirup Markisa Berastagi - Suprianto; Muhammad Gunawan; Melati Yulia Kusumastuti; Cut Fatimah; Debi Meilani (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Fruit syrup is made from a sugar solution, the taste and aroma are determined by the freshness of the fruit. Fruit commonly used in making syrup has an attractive color, aroma and distinctive taste. Passion fruit (Passiflora edulis Sims.) has a distinctive taste and aroma, so it is widely processed into syrup. This study was to evaluate CMC and Agar-Agar stabilizers in the passion fruit syrup formula. Evaluation includes color, appearance, texture, taste and aroma and hedonic tests are carried out. The results showed that there were significant differences in the color, appearance, texture, taste and aroma of passion fruit syrup. Stabilizers CMC and Agar-Agar make the color, texture and appearance of the syrup better and more attractive. The result of hedonic test for ideal syrup concentration is S3 with 4 g of Agar and 6 g of CMC. The higher the concentration of CMC and Agar, the greater the viscosity of the syrup. The concentration of CMC and Agar-agar in a mixture of fruit juices gave significantly different effects on color, texture, appearance, taste and aroma